Representation of Minangkabau in the film Onde Mande! - Herry N Hidayat; Okta Firmansyah (LPPM Institut Seni Indonesia Padangpanjang, 2025)
This article describes the results of the film study on Onde Mande! (2023, Paul Fauzan Agusta). In general, this film tells the story of the conflicts and intrigues that occurred among residents on the shores of Lake Maninjau who intended to build their village. However, there is a discourse in the story's structure. This film's narrative structure does not only show Minangkabau's life and culture. In this research, the film Onde Mande! is seen as the language behavior of a social group. The analysis technique is based on the storytelling structure, which includes characterization, setting, and focalization (point of view). The characters' actions are analyzed through screenshots and divided into categories of sequential scenes. The results of both analyses are then analyzed further by viewing it as a representation of a society, in this case, the Minangkabau, through the symbols in the film. As a result, the narrative of this film builds the character of the Minangkabau people, who are proud of their Minangkabau heritage. They are willing to sacrifice for the progress and prosperity of their hometown. On the other hand, the meaning of the emerging symbols builds up a discourse on power relations. This film creates the impression of social protest against the reigns. The ruler's inability to improve the welfare of his people must be paid for by the fraudulent actions of members of his society.